Superconductivity without dependence on valence electron density in (Al, Zn, Co) doped YBCO systems - Yufeng, Zhang; Dandan, Wang; Pinglin, Li (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We adopted the x-ray diffraction, oxygen contents, positron annihilation technology and simulation methodsto investigate systematically YBa2Cu3–x(Al, Zn, Co)xO7–δ (x = 0–0.5) cuprates. The experimental results and simulated calculations support the existence of cluster effect. Moreover, it is concluded that the cluster effect is an important factor on suppression of the superconductivity and the Tc does not depend directly on the density ofvalence electron in the samples.